REVITALISASI USAHA MIKRO DI DESA GANDU MELALUI PENERAPKAN STRATEGI BISNIS YANG EFEKTIF UNTUK PERTUMBUHAN BERKELANJUTAN - Amilia Yuni Damayanti; Arief Rahmawan; Khurun'in Zahro'; Akhmad Affandi Mahfudz; Royyan Ramdhani Djayusman (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Microenterprises (MSEs) in Gandu Village have great economic potential, but still face challenges in improving competitiveness and sustainable growth. The main problems faced by UM actors include limitations in preparing business strategies, inefficient production management, and low utilization of digital technology in marketing. One of the businesses facing these challenges is Bu Nor's Krecek Krupuk UM. The purpose of this service activity is to increase partners' capacity in formulating effective business strategies, increasing production efficiency, utilizing digital technology for marketing, and improving financial management to encourage sustainable business growth. The method used is a participatory approach through three stages: preparation, implementation, and evaluation, which actively involves partners in the entire process. The results of this activity show an increase in the understanding and skills of business actors in developing business strategies, applying digital marketing techniques, and improving production management. Post-training evaluation shows that the strategies that have been developed are able to help businesses increase production capacity and competitiveness in the market. With this training and mentoring, UM Krecek Krupuk Bu Nor is expected to develop sustainably, improve the quality and quantity of its products, expand its marketing reach, and increase its income.